A comparative study of caudal epidural bupivacaine with bupivacaine plus fentanyl and bupivacaine plus neostigmine for anaesthesia and postoperative analgesia in children undergoing sub-umbilical surgeries - Rahman, Mizanur; Rahmn, Md Habibur; Kamrujjaman, Md; Islam, Md Shafiqul (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background: Single-shot caudal anaesthesia with local anaesthetic has a limited duration of action.Therefore, many children undergoing sub-umbilical surgery with caudal analgesia require furtheranalgesia during the postoperative period. This study compared the effect of single-dose caudal epiduralbupivacaine, bupivacaine plus fentanyl and bupivacaine plus neostigmine for anaesthesia andpostoperative analgesia in children. Objective: To evaluate effectiveness of bupivacaine with the addition of fentanyl or neostigmine forcaudal anaesthesia and analgesia in children undergoing sub-umbilical surgeries. Methods: Total ninety (90) paediatric patients, aged 2-8 years with ASA(American society ofanesthesiologist) grades I & II who were scheduled for surgery in Sher-E-Bangla Medical college Hospital,Barisal were included in this study. Data were collected by using a pre-designed questionnaire. Thepatients were randomly allocated to one of the three groups. Group A was received caudal 1 ml/kg ofbupivacaine 0.25%, Group B 1 ml/kg of bupivacaine 0.25% with fentanyl 1 μg/kg and Group C 1 ml/kgof bupivacaine 0.25% with neostigmine 2 μg/kg. Heart rate (HR), Blood pressure (BP), oxygen saturation(SpO2), Respiratory rate (RR) were recorded during operation and every five minutes thereafter. Theduration of analgesia was defined as the time from caudal injection to first dose of rescue analgesia.Rescue analgesia was given for an objective pain scale (greater than or equal to) 4 in the form of oralparacetamol (15mg/kg). Results: Assessment of anaesthesia was significantly longer in the two groups of children who receivedadditives compared with local anaesthetics group alone (p<0.01). Mean time to first postoperativeanalgesic administration was 167.37±17.30 min, 280.57±14.40min, and 357.77±19.08 min in groupA, Group B, and group C respectively. The difference was statistically significant (p<0.01) between thethree groups. In these cases duration of analgesia was considered from the placement of caudal to firstanalgesia. Conclusion: Addition of fentanyl or neostigmine to bupivacaine prolonged the duration of surgicalanaesthesia and postoperative analgesia after a single shot caudal injection with minimal incidence ofside effects in children undergoing sub-umbilical surgeries. This could be a safe and cheap alternative toextradural catheter placement for surgical procedures of intermediate duration. JBSA 2019; 32(1): 3-9